ANALISIS PERSEPSI MASYARAKAT TERHADAP PERAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENGENDALIAN KEBAKARAN HUTAN (STUDI KASUS KARHUTLA DI DESA SALO KECAMATAN SALO KABUPATEN KAMPAR PROVINSI RIAU 2019) - Anggi Nabila Balqis; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the natural disaster of forest fires thatoccurred in the village of Salo subdistrict of Kampar District of Riau Province whichoccurred in 2019 even though there was already a (BPBD) tasked with controlling andpreventing natural disasters that occurred in Kampar district. In carrying out regionaldisaster management there are tasks that must be carried out by BPBD. Theformulation of the problem in this study is